Meningkatkan Prestasi Belajar Siswa Melalui Bimbingan Orang Tua di Rumah - Julia Ismail; Widya Azahara; Nurhani Mahmud (Peneliti.net, 2021)
This study aims to determine the increase in student achievement through parental guidance at home. The population in this study were all students of class V MIS Hi. Achmad Syukur Daruba, totaling 30 students. The sample in this study amounted to 30 students or the entire population. This study uses a percentage quantitative descriptive method with data collection techniques using questionnaires, interviews and documentation. The data analysis in this study used the presentation formula and the presentation interval scale. Based on the results of the study it can be concluded that, this study is in the